Variable‐structure copula model for multi‐scenario bi‐level transmission and generation expansion planning. Issue 21 (3rd September 2022) - Wang, Yurong; Yang, Ruolin; Li, Fangxing; Tang, Yi; Zhao, Xin
Abstract: With the large‐scale integration of renewable energy into power systems, the strong correlation of wind power output as an important feature will inevitably bring huge impact on power grid planning and operation. However, due to the proliferation of planning and operation scenarios, the traditional power grid planning method can no longer guarantee the operation flexibility and stability under the fluctuation of new energy. In this work, a bi‐level transmission and generation expansion planning (TGEP) model considering the correlation of wind power based on mixed integer linear programming (MILP) is proposed. Firstly, a variable‐structure point diagnosis method is proposed to improve the fitting accuracy of the correlation. Secondly, a scenario reduction method considering the correlation, joint probability distribution and geometric characteristics is proposed, which effectively provides a more matching operating scenarios basis for planning. Thirdly, a multi‐scenario bi‐level TGEP model is proposed. The upper‐level investment decision model aims at the economical goal, while the lower‐level multi‐scenario coordinated optimization operation model aims to minimize the weighted operation index. The impact of the correlation on the results of TGEP is examined and verified in case study.